The cis-regulatory effect of an Alzheimer's disease-associated poly-T locus on expression of TOMM40 and APOE genes - Linnertz, Colton (2014)
INTRODUCTION: We investigated the TOMM40-APOE genomic region that has been associated with the risk and age of onset of late-onset Alzheimer's disease (LOAD) to determine if a highly polymorphic, intronic polyT within this region (rs10524523, hereafter 523) affects expression of the APOE and TOMM40 genes. Alleles of this locus are classified: short-S, long-L, very long-VL based on the number of T-residues. METHODS: We evaluated differences in APOE-mRNA and TOMM40-mRNA levels as a function of 523 genotype in two brain regions from APOEε3/3 Caucasian autopsy-confirmed LOAD cases and normal controls. We further investigated the effect of the 523 locus in its native genomic context using a luciferase expression system. RESULTS: The expression of both genes was significantly increased with disease. Mean expression of APOE and TOMM40-mRNA levels were higher in VL-homozygotes compared to S-homozygotes in temporal and occipital cortexes from Normal and LOAD subjects. Results of a luciferase reporter system were consistent with the human brain mRNA analysis: the 523-VL polyT resulted in significantly higher expression than the S-polyT. While the effect of polyT length on reporter expression was the same in HepG2 hepatoma and SH-SY5Y neuroblastoma cells, the magnitude of the effect was greater in the neuroblastoma than in the hepatoma cells, which implies tissue-specific modulation of the 523-polyT. CONCLUSIONS: These results suggest that the 523 locus may contribute to LOAD susceptibility by modulating the expression of TOMM40 and/or APOE transcription.